The Influence of Using Printed Mass Media on the Students Reading Comprehension - Harya, Trisna Dinillah (Attractive : Innovative Education Journal, 2022)
Newspapers as part of printed mass media is become one of the printed media that can help the students to comprehend the text easily. The objectives of this research were to know whether Printed Mass Media influence the students’ reading comprehension ability among the eleventh grade of MadrSasah Aliyah Nurul UlumPayungRejo Central Lampung. To collect the data the researcher used test, observation and documentation, to get the students’ score the researcher used written test in multiple choice form. In this research, the researcher used Quantitative research. It aimed to find out whether by using Printed Mass Media could influence the students’ reading comprehension ability. This research involved students with given pre-test, treatment and post-test. The researcher used T-test formula to analyze the data. Finally, the data indicated that Tobserved = 19,564 was higher than Ttable = 2,042 (5%), and 2,750 (1%). It means that Printed Mass Media can give positive and significant influence on the students’ reading comprehension ability among the eleventh grade of Madrasah Aliyah Nurul UlumPayungRejo Central Lampung. Keywords: Students Reading Comprehension, Printed Mass Media, Reading Comprehension